From Anxiety to Independence: Disability Empowerment Innovation through the Superior Disability Teaching Center (PADU) Program - Shafira Ramadhani; Qadri Karim; Nindya Sari (Buletin Antropologi Indonesia, 2025)
Persons with disabilities in Bitung City, particularly the Deaf community, continue to face limited access to education, employment, and social participation. In response, PT Pertamina Patra Niaga, through its Corporate Social and Environmental Responsibility (TJSL) program, implemented a participatory and collaborative approach that included surveys, interviews, focus group discussions (FGDs), and observations, accompanied by pre- and post-test evaluations to measure participants' competency improvement. The PADU Program offers five main training modules — Sign Language, Souvenir Production, Barista Skills, Shoe Care, and Digital Creativity — tailored to the diverse types of disabilities among participants. The results indicate an average increase of 40% in technical skills and 35% in social aspects, including self-confidence and communication. Economically, participants successfully produced approximately 200 coconut-shell souvenirs, valued at around IDR 10 million per month. The program also contributed to reducing potential emissions by up to 15 tons of CO₂ per month through the implementation of a circular economy approach. PADU contributes to SDGs 8, 10, 12, and 13, demonstrating that multi-stakeholder collaboration can foster inclusive, equitable, and sustainable social transformation for persons with disabilities. The Bitung Deaf Care Community (KALEB) established the PADU Inclusive Disability Learning Center as a community-based model for inclusive empowerment. This study employs a qualitative approach.